Telehealth Can Be Implemented Across a Musculoskeletal Service Line Without Compromising Patient Satisfaction. Issue 1 (February 2021) - Greenfield, Paul T.; Manz, Wesley J.; DeMaio, Emily L.; Duddleston, Sage H.; Xerogeanes, John W.; Scott Maughon, T.; Spencer, Corey C.; Dawes, Alexander; Boden, Scott D.; Hammond, Kyle E.; Wagner, Eric R.; Gottschalk, Michael B.; et al.
Background: The COVID-19 pandemic has led to changes to in-office orthopedic care, with a rapid shift to telemedicine. Institutions' lack of established infrastructure for these types of visits has posed challenges requiring attention to confidentiality, safety, and patient satisfaction. Purpose : The aim of this study was to analyze the feasibility of telemedicine in orthopedics during the pandemic and its effect on efficiency and patient satisfaction. Methods : Patients seen by the Emory University Department of Orthopaedics Sports Medicine and Upper Extremity Divisions via telemedicine from March 23 to April 24, 2020, were contacted by telephone. Each patient was asked to respond to questions on satisfaction, ease of use, and potential future use; satisfaction with telemedicine and previous clinical visits were measured using a modified 5-point Likert scale. Results : Of the 762 patients seen, 346 (45.4%) completed the telemedicine questionnaire. Satisfaction varied by visit type, with average scores of 4.88/5 for in-office clinic visits versus 4.61/5 for telemedicine visits. There was no significant difference among age groups for satisfaction ratings. Patients 65 years old or older reported significantly longer visit times and decreased ease of use with the telemedicine platform. Conclusion : Telemedicine in a large orthopedics department was successfully implemented without compromising patient satisfaction. The use of telemedicine allows many patients to be seen quickly and efficiently without diminishing their musculoskeletal clinical experience.